La fuerza vinculante de la jurisprudencia del Consejo de Estado (2018)
Constitutional jurisprudence is considered a formal and material source of law in the Colombian legal system, hence its binding force in the decisions of judicial and administrative authorities. This recognition, derived from the judicial function of the Constitutional Court, does not occur in the contentious-administrative jurisdiction, since the Council of State has not managed to make a diligent issuance, compilation and publication of decisions with a binding character. This investigation focuses its attention on the contentious-administrative jurisdiction and on the binding nature of jurisprudence originating from the Council of State. Herein are studied new legal figures contemplated in Law 1437 of 2011 such as the duty of uniform application of jurisprudence, the extension of the jurisprudence of the Council of State to third parties by authorities, the extraordinary appeal of unification of jurisprudence and the judgments of unification.The binding nature of the judgments of unification issued by the Council of State is established in accordance to this law. It also shows how, if the application is achieved of the new figures and procedures studied, it will contribute to the recognition of the binding force of jurisprudence from the Council of State, clearing backlogs and protecting important values of the legal system, as well as equality of treatment and legal certainty in contentious-administrative issues.